Cingulin is an RNA-binding protein promoting pancreatic cancer through enhancing importin 7-mediated phospho-ERK nuclear translocation - Yuling Su; Fang Wei; Shu Li; Jiaming Qi; Guohuan Lin; Guantuo Li; Ping Liang; Zhenwei Yang; You Long; Xiaojia Li; Tingting Jiang; Jie He; et al. (Cell Reports)
Summary: Pancreatic ductal adenocarcinoma (PDAC), a lethal malignancy with difficult early diagnosis and poor prognosis, urgently requires elucidation of the molecular determinants dictating pancreatic cancer initiation and progression. Little is known about cingulin (CGN) in carcinogenesis. In this study, we demonstrated the critical oncogenic role of CGN in PDAC pathogenesis. Increased expression of CGN promoted pancreatic acinar-to-ductal metaplasia (ADM), and CGN is progressively upregulated during PDAC initiation and progression. CGN was required for PDAC cell proliferation, gemcitabine (GEM) resistance, tumorigenesis, and metastasis, and its overexpression predicted a poor patient prognosis. Mechanistically, CGN, as an RNA-binding protein, stabilizes the mRNAs of AXL and importin-7 (IPO7), activating the mitogen-activated protein kinase (MAPK)/extracellular regulated protein kinase (ERK) signaling and promoting the nuclear translocation of phosphorylated ERK (pERK), which facilitates the malignant behavior of PDAC cells. Therefore, our study has demonstrated that CGN forms an oncogenic signaling axis, which could be an effective therapeutic target for PDAC treatment.